Addressing the Resource-Based View: Determinants That Drive Chinese Universities to Offer MOOCs - Kai Wang; Josep Rialp Criado; Stefan Felix van Hemmen (International Review of Research in Open and Distributed Learning, 2024)
This study involved 51 Chinese universities from the Quacquarelli Symonds (QS) World University Ranking 2021. With based the resource-based view (RBV) as a framework, it aimed to identify the determinants of human resource capital that were related to universities’ production of MOOCs. Three determinants were detected—size, lifelong learning, and proximity to the political centre. Both size and proximity to the political centre proved to be significant. The findings provide timely implications for university managers and suggest that the variety of management spaces be expanded to increase the portfolio of high-quality Chinese universities that facilitate the production of MOOCs. In addition, universities should increase their proximity awareness to remedy the disadvantages of uneven resource allocation due to geographical proximity.